Rare Diseases of Neurodevelopment: Maintain the Mystery or Use a Dazzling Tool for Investigation? The Case of Rett Syndrome. (15th July 2020) - Ruffolo, Gabriele; Cifelli, Pierangelo; Miranda-Lourenço, Catarina; De Felice, Eleonora; Limatola, Cristina; Sebastião, Ana M.; Diógenes, Maria J.; Aronica, Eleonora; Palma, Eleonora
Abstract: The investigation on neurotransmission function during normal and pathologic development is a pivotal component needed to understand the basic mechanisms underlying neurodevelopmental pathologies. To study these diseases, many animal models have been generated which allowed to face the limited availability of human tissues and, as a consequence, most of the electrophysiology has been performed on these models of diseases. On the other hand, the technique of membrane microtransplantation in Xenopus oocytes allows the study of human functional neurotransmitter receptors thanks to the use of tissues from autopsies or surgeries, even in quantities that would not permit other kinds of functional studies. In this short article, we intend to underline how this technique is well-fit for the study of rare diseases by characterizing the electrophysiological properties of GABAA and AMPA receptors in Rett syndrome. For our purposes, we used both tissues from Rett syndrome patients and Mecp2-null mice, a well validated murine model of the same disease, in order to strengthen the solidity of our results through the comparison of the two. Our findings retrace previous results and, in the light of this, further argue in favor of Prof. Miledi's technique of membrane microtransplantation that proves itself a very useful tool of investigation in the field of neurophysiology. This article is part of a Special Issue entitled: Honoring Ricardo Miledi - outstanding neuroscientist of XX-XXI centuries . Highlights: EGABA is less hyperpolarizing in both Rett syndrome and animal model of the same disease. Bumetanide is able to restore the EGABA to values similar to controls. AMPA/GABA ratio pattern is similar in both Rett syndrome and Mecp2-null mice.